Combined Resective and Regenerative Therapy - A Novel Approach in the Management of Furcation Involvement: A Case Report - Amruth Ganesh; Jyosthna Ganapathi Madhurkar; Shashikanth Hegde; Sneha Bhat; Haziel Jenifer (Journal of Multidisciplinary Dental Research)
Periodontal furcation involvement represents a challenge in the treatment of periodontally compromised molars. Different treatment modalities are advocated in the treatment of FI including non-surgical therapy, resective and regenerative treatment, according to subject and site factors and degree of involvement of individual affected molars. The aetiology of FI include anatomic factors, extension of inflammatory periodontal disease, trauma from occlusion, pulpo periodontal disease and root fracture involving furcations. An emerging approach to periodontal therapy is a concept of regeneration. In this case report a novel combination therapy of a blend of platelet rich fibrin with bone graft was used in the management of grade III furcation involvement. Results showed successful outcome in terms of esthetics and function. Keywords: Root resection, Furcation involvement, Bone graft, PRF